Kidos Travel Kit (Kidos Cov-19 Protection Kit ) / Nur Ilyana Syuhada Mohd Nazri - Mohd Nazri, Nur Ilyana Syuhada (2022)
Kidos Travel Kit is a new prod- uct proposed which may help every parents for their kids to go travel. Thus, this product purpose is to encourage and ease for every kid to be alert to the environment of Covid-19 is a serious illness.